Wood detritus: A functional concept in interior design - Evans Kwadwo Donkor (Nilay ÖZSAVAŞ ULUÇAY, 2021)
The cutting of trees for site construction and development had become a predominant factor in Ghana. Besides, the practice of cutting and leaving tree roots in the soil had become an impediment, such as harbouring wild reptiles like snakes, iguanas and an infestation of termites. These factors endanger individual lives, especially living in such environments. This study focused on repurposing wood detritus as a functional concept in the interior design. The study sought to analyse neem tree roots and their properties for a decorative piece in interior design. As a studio-based inquiry, the study employed the aesthetico-action model with a narrative method on the techniques and procedures for executing the studio work. It was evident from the studio practice that wood detritus such as neem tree root serves as an embodiment of inherent qualities, ideas and artistic expressions based on its roots' natural forms. Artists should focus on tree roots (stumps) left in the soil and on the environment as a material for art production in the interior space design.